2012
DOI: 10.1177/230949901202000218
|View full text |Cite
|
Sign up to set email alerts
|

Kirschner Wire Fixations for Scapholunate Dissociation: A Cadaveric, Biomechanical Study

Abstract: purpose. To compare 5 different Kirschner wire fixation techniques in terms of the failure loads seen as scapholunate (SL) dissociation in a cadaveric, biomechanical study. Methods. 10 fresh-frozen, finger-amputated wrists with sectioned SL ligaments from 3 male and 2 female cadavers were tested. The change of SL angle, SL dissociation, and the load to failure of the 5 different Kirschner wire fixation techniques (using 1.4-mm Kirschner wires) were compared using an axial loading testing machine. The technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This pinning technique has been shown to be the strongest method. 38 The ligament is then repaired using free needles, sutures, osteosutures and/or bone anchor sutures, depending on the type of injury. In some cases, it is easier to place the sutures into the ligament prior to the final reduction and then simply tie them all once the SL joint has been reduced and stabilised.…”
Section: Anatomymentioning
confidence: 99%
“…This pinning technique has been shown to be the strongest method. 38 The ligament is then repaired using free needles, sutures, osteosutures and/or bone anchor sutures, depending on the type of injury. In some cases, it is easier to place the sutures into the ligament prior to the final reduction and then simply tie them all once the SL joint has been reduced and stabilised.…”
Section: Anatomymentioning
confidence: 99%
“…[5][6][7][8]Open repair of the SL ligament and SL joint xation with multiple Kirschner-wires has been shown to produce good mid-term outcomes with brosis union of the ligament. [12,14,15] However, postoperative loss of range of motion and potential degenerative wear of radio-scaphoid joint are possible complication. Tendon reconstruction has also been reported as an alternative to replace the unrepairable SL ligament, but this procedure is technically challenging.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that the SLLC is the primary stabilizing element of the SLJ (Short et al, 2009). Authors including Brunelli have proposed that complete sectioning of the SLLC on cadaver wrists will never reproduce the kinematics of scapholunate dissociation (Brunelli, 2003), while other authors have suggested that a level of loading in excess of the physiologic 5 N (Jakubietz et al, 2012), or repetitive motions (Short et al, 2009) to the injured wrist are needed to observe a measurable effect. Using a highly accurate magnetic tracking device in our study, we were able to observe significant differences, even without those preconditions.…”
Section: Discussionmentioning
confidence: 99%